Intensive Outpatient Treatment of Depression in a Spinocerebellar Ataxia Type 1 Patient - Eric Black (Case Reports in Psychiatry)
Objective. Spinocerebellar ataxia type 1 (SCA1) is but one subtype of spinocerebellar ataxia (SCA), each of which can possibly be considered a separate neurological condition (N. Whaley, S. Fujioka, Z. K. Wszolek, 2011). SCA is hereditary, progressive, and degenerative. SCA1 symptoms initially include coordination problems and ataxia. SCA1 can also include speech and swallowing difficulties, spasticity, ophthalmoplegia, cognitive difficulties, and even sensory neuropathy, dystonia, atrophy, and fasciculations. Literature has established that depressive symptoms can be exhibited with spinocerebellar ataxia patients regardless of type (T. Schmitz-Hübsch, 2011). While a higher risk for depression occurs with more severe SCA disease, successful treatment to mitigate symptoms has been documented (N. Okamoto, M. Ogawa, Y. Murata, et al., 2010). In this case a SCA1 patient with advanced neurological disease was enrolled in a psychiatric intensive outpatient (IOP) treatment program in the midwestern United States to address his comorbid depressive symptoms. This treatment option allowed a less restrictive environment while providing a more structured therapeutic setting and social support for the patient, much more so than that which is typically offered in a traditional outpatient setting. Case Report. A patient with relatively advanced SCA1 successfully participated in a psychiatric IOP program or depressive symptoms and benefitted from the program’s structure and additional psychosocial support. Conclusion. Awareness among physicians, particularly psychiatrists and neurologists, regarding IOP programs as a treatment option for comorbid depression in the clinical setting of progressive SCA or other neurological conditions can be beneficial to patients requiring an increased level of psychiatric treatment.